Intellectual property: theorizing and empirical analysis - Valeriy Nikolayevskyy; Viktoriia Omelchenko; Olena Bakalenko (Український соціологічний журнал, 2020)
The authors of the article based on the understanding of intellectual property as an immanent component of the innovative economy, an important factor, resource and mechanism of innovation environment and development, note the actualization of this phenomenon in nowadays society of revolutionary technological changes. The article deals with the brief overview of the some features and characteristics of the process of reforming the institute of intellectual property in Ukraine, including regulatory framework, and also is based on the analysis of data gathered in sociological survey «Intellectual property through the eyes of university lecturers and high school teachers», conducted during May-December 2019, method – interview; n = 356. Based on the research results, the authors analyze high school teachers’ and university lecturers’ attitudes to the intellectual property, the factors and mechanisms of protection of intellectual property rights. What are the attitudes towards violation of intellectual property rights in the field of education? How acute is the problem of intellectual property rights (IPR) violation for the participants in the educational process? Is the impact of intellectual property rights violation noticeable on their (high school teachers and university lecturers) day-to-day activities? Who, what institution (organization) should make efforts to protect IPR? These and some other issues are analyzed in the paper. The authors note, among other, that, in general, the problem of IPR violations perceived as quite acute for many (relative majority) of university lecturers and high school teachers, the impact of this problem on respondents’ daily activities is mostly negative. Opinions of respondents on the institution(s), which should make efforts to protect IPR were clarified. Analysis of possible ways (inner and external factors, mechanisms) to enhance the level of protection, public management of the protection process, as well as the development of a culture of IPR is presented also. The authors propose the prospects for further research of the problem.